A pragmatic analysis of American cuisine - Mamatqulova , Fotima (The Lingua Spectrum, 2025)
Food reviews and comments are a rich form of cultural communication, in which participants verbally and nonverbally express their experiences and opinions about food. Expressions made after tasting a meal can vary between those who have a positive (“culinary fans”) and those who have a negative (“culinary critics”) opinion of the food served. Audiences can recognize differences between the profiles of critics and fans based on sociodemographic and behavioral characteristics. In a global context of increasingly interconnected sociodemographic and behavioral characteristics, it is interesting to see the intercultural pragmatic approach to language expression in food reviews by the American community to improve cross-cultural language proficiency.